Post-Publication Review: Evolution of the Scientific Publishing Workflow - D. M. Kochetkov (Ekonomika Nauki)
For a considerable period of time, peer review has been regarded as the cornerstone of academic journals and scientific communication, ensuring the high quality and reliability of published materials. However, in the early decades of the 21st century, a growing number of scholars began to challenge the traditional peer review procedure, questioning its efficacy. This study aims to provide a fresh perspective on the peer review mechanism, with the objective of enhancing the implementation of scientific communication's functionalities. The research employs historical analysis techniques and modelling methods based on Business Process Model and Notation (BPMN) to compare diverse review models in terms of their influence on scientific communication. BPMN is a conventional tool employed for modelling and describing business processes. The evolution of the peer review procedure is explored, encompassing an examination of the factors contributing to current and future transformations in the publishing realm. The author refers to the crisis of the conventional peer review system and the growing prevalence of preprints, serving as exemplars of these transformations. Finally, suggestions for the implementation of the post-publication review workflow in Russia are provided.